Sinergi Penghijauan dan Penerangan Jalan untuk Pembangunan Berkelanjutan Desa Sasak Panjang - Anwar, Syaiful; Hamzah, Zeze Zakaria; Khoirunnisa, Darin Hanifah; Nisa, Reysa Amelia; Hafiz, Muhammad Haiqal (Universitas Pahlawan Tuanku Tambusai, 2026)
This community service program was conducted to address environmental issues and nighttime safety concerns in Sasak Panjang Village through the synergy of greening initiatives and street-lighting improvements. The main objective was to enhance environmental quality, comfort, and residents’ sense of security using a community-based participatory approach. The methods included public outreach, mapping priority locations, planting shade trees, and installing energy-efficient street lights in collaboration with village officials and community groups. The results show increased vegetation density in public areas, reduced dark and vulnerable spots, and greater evening community activities. The integration of both programs effectively strengthened village sustainability by improving living-space quality and fostering social interaction. These findings highlight that collaboration between the community and village government is essential for achieving sustainable development at the local level.